‘THINKERS TALK’: AN IDEA-SHARING PLATFORM FOR USM COMMUNITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 13 August 2016 – The ‘Thinkers’ Talk’ Programme organised by the Universiti Sains Malaysia (USM) Idea Bank is hoped to become a platform for the USM community in spurring constructive ideas for the development of the university, as well as in being one of the channels to assist the university in facing 2016.